AN ITEM ANALYSIS OF THE ENGLISH SUMMATIVE TEST FOR THE SEVENTH GRADE STUDENTS OF SMPN 12 TANGERANG SELATAN - Rosyad, Sabilar (AKSELERASI: Jurnal Ilmiah Nasional, 2024)
The objective of this study is to find out whether or not the English summative test for the Seventh Grade Students of SMPN 12 Tangerang Selatan can be categorized as a good test based on the difficulty level, the discriminating power and the effectiveness of distracters. The respondents of this study were the seventh grades students of SMP Negeri 12 Tangerang Selatan. The respondents of this study were taken from two classes. The number of this population was 68 students. The students of each class consist of 38 and 30 students. The number of sample of this study was 34 respondents, 17 respondents of the upper group and 17 respondents of the lower group. The method of the study was descriptive quantitative and qualitative method. In analyzing the difficulty level and the discriminating power, the writer used the formula suggested by Heaton to analyze the difficulty level and the formula suggested by Hopkin and Antes to analyze the discriminating power. After analyzing the difficulty level, there have been 24 items which categorized in the easy level, 24 items which categorized in the medium level, and 2 items which categorized in the difficul level. In terms of the discriminating power, there have been 37 items can be accepted, 10 items should be revised, and 3 items should be discarded. Based on the results of the difficulty level and the discriminating power, it can be concluded that the test fulfills the criteria of a good test.